Learning collocations: Effects of online tools on teaching English adjective-noun collocations - Basal, Ahmet (WILEY, 2019)
Collocations are word combinations essential for achieving fluency in a given language. Considerable emphasis should therefore be placed on teaching collocations as a part of vocabulary instruction in language teaching. However, there is no current consensus on how best to teach collocations, and few studies have addressed the issue. This quasi-experimental study investigated the effectiveness of online tools for learning English adjective-noun collocations compared to learning collocations via traditional activities. A quasi-experimental design with a pretest and immediate and delayed posttests was applied to 53 participants (n = 25 for the control group; n = 28 for the experimental group). The test results reveal that participants in the experimental group who learned collocations with online tools performed significantly better on both immediate and delayed posttests, demonstrating the effectiveness of these tools on learning adjective-noun collocations.
Keywords: DICTIONARY USE; VOCABULARY; LANGUAGE; STUDENTS; ACQUISITION; LEARNERS; CONTEXT; Education & Educational Research